Perbedaan Tingkat Berpikir Construal Terhadap Kontrol Diri Pada Mahasiswa - Nurfitriany Fakhri (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
This study aims to determine the differences in the construal level thinking of the self-control on the students of the Faculty of Psychology at the State University of Makassar. This study used a comparative method to determine how much the role of different levels of thinking construal on self-control, with a total sample of 60 subjects. The population of this study were students of Psychology UNM faculty. Data collected by the BIF scale and self-control scale. The data which had collected, then, analyzed using statistical analysis Independent Sample T-Test. The results showed that there are differences in the level of construal thinking on self-control, where individuals who develop a high -level construal thinking will tend to have better self-control, compared with individuals who developed a low-level construal of thinking.